FAKTOR-FAKTORoYANG BERHUBUNGAN DENGAN KEJADIANoKECELAKAAN KERJAoPADAoKARYAWAN NON MEDIS DI INSTALASIoGIZI RSoX DI PURWODADI - Lela Vista Atrika Sari Waoma; Baju Widjasena; Daru Lestantyo (Jurnal Kesehatan Masyarakat (Undip), 2018)
Hospital nutrition installationzis a vulnerable place that has high accident risk because there are manyzdangerous types ofzequipment and environmental conditions that couldzjeopardized the worker. The objective of this research was to analyzed the relations between variables of accident, zexhaustion, occupational safety and health training, occupationalzsafety and health procedure, workplace environment, room temperature and type of education with workplace accident. This research waszanalytic descriptive with a cross-sectional approach. The population of this research was food handler of X hospital in Purwodadi amounting to 22 peoplezused total sampling technique. The data collection was done by fulfilling the accident, exhaustion, occupational safety and health training, occupational safety and healthzprocedure, workplacezenvironment, zroom temperature and type of education questionnaire and also assessing the room temperaturezusing heatzstresszmonitors. Data analysis using the chi-square test. The result shows that there was  relationship between exhaustion (p-value = 0,003), occupational safety and health training (p-value = 0,03), zoccupational safetyzand health procedure (p-value = 0,003), zworkplace environmentz (p-value = 0,001), room temperaturez (p-value = 0,003), type of education (p-value = 0,003) with workplace accident on foodzhandler in nutrition installation. The management should hold briefing routinely, hold an appropriate occupationalzsafetyzand health training, and do supervisionzto improve the employeezskills and the employee could obeyzthe occupational safety and healthzprocedure.